Sistem Informasi Ekstensibilitas E-Commerce Berdasarkan Data Trafik Menggunakan Statistik Proses Kontrol - Gunawan, Andi; Mustafid, Mustafid; Sugiharto, Aris (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
The concept of quality control has been widely used in companies for the fulfillment of customer satisfaction on products produced. Loss of customers due to in appropriate quality standards are important avoided by the company. This study aims to establish quality control information system e-Commerce in the diagram view map control. In this study, it is used Statistic Process Control (SPC) method. In the early stages, e-Commerce is assumed to have  met  with quality variable of EWAM  method. Transaction visitation opportunities at a certain period used as a parameter of quality, and is called extensibility. The visitation data were collected by web traffic and applications and transaction data that occur in e-Commerce. Waterfall model approach was used in the prototype development process. The results of this  study  was  the  extensibility  of  e-Commerce  information  system.  Automation  of  data  collection  occurs  in  real  time  information system, so  that the e-Commerce extensibility statements can be  continuously  monitored. Analysis of results displayed by the  control chart suggested that a sustain effort in the control of extensibility can provide benefits in an effort to retain customers while management can  use  number  of  extensibility  variable  in  increasing  profitability  of  the  company  or  the  consideration  of  using  e -Commerce. Completion  of  e-Commerce  extensibility  can  gradually  be  increased  through  the  reduction  of  extensibility  variation,  while  the improvement of extensibility relies on the reparation of e-Commerce systems associated with EWAM variable.Keywords : E-Commerce; Web traffic; Extensibility;  Quality control; Automation